Avaliação da influência do perfil de saúde do idoso no equilíbrio e na eficácia da intervenção fonoaudiológica para tontura - Rosa, Luiza Diniz da (2021)
INTRODUCTION: Rotatory dizziness and imbalance are frequent among the elderly and many factors can influence the occurrence of this symptom. OBJECTIVE: To identify the heterogeneous characteristics of elderly people with dizziness and compare these characteristics to their health profile. METHOD: This is an observational and cross-sectional study, which analyzed questionnaires and evaluated the characteristics of each subject. The sample consisted of 40 elderly people of both genders, aged between 60 and 90, with complaints of dizziness. In addition to the Multidimensional Geriatric Assessment, we used anamnesis on general health status and dizziness, a social data questionnaire, a Mini-Mental State Examination, the Lawton Scale, the Gait Speed Test, the Geriatric Depression Scale, the Dizziness Handicap Inventory and a quantitative evaluation of dizziness. We also assessed the subjects’ audiometric thresholds. For the purpose of bivariate and multivariate analysis (Poisson regression models), the participants were divided into two groups according to their health profile: healthy and pre-fragile or fragile. RESULTS: Among the 40 elderly patients, 85% (n = 34) were female and 15% (n = 6) male, with a mean age of 71.08 and a standard deviation of 9.08 years. Out of the total, 25% (n = 10) were considered healthy, 55% (n = 22) pre-fragile and 20% (n = 8) fragile. Dizziness was the main chronic symptom, as 75% (n = 30) reported having the problem for more than one year. As for the type of dizziness, 25% (n = 10) reported feeling associated symptoms of vertigo and instability, 37.5% (n = 15) reported feeling only vertigo and 37.5% (n = 15) reported instability only. For statistical analyses, we created two groups: healthy (n=10) and pre-fragile + fragile (n=30). Bivariate analyses (Anova, chi-square, and Mann Whitney) identified the most frequent variables for the elderly in the prefrail/frail group: gait deviations, episodes of falls, more than one chronic disease, more hearing difficulties, slower gait speed, and physical limitations, among others. However, these were the variables in the regression model for the pre-frail and frail elderly adjusted for age: gait speed (p <0.001), the presence of more than three chronic diseases (p = 0.039), and the report of spine problems (p = 0.016). CONCLUSION: Elderly people with a pre-frail and frail health profile were more prone to develop health conditions, had greater physical limitations, a greater degree of dependence, and slower gait speed, which increases their risk of falling